Ultrasound Imaging in Sport-Related Muscle Injuries: Pitfalls and Opportunities - Marco Paoletta; Antimo Moretti; Sara Liguori; Francesco Snichelotto; Ilaria Menditto; Giuseppe Toro; Francesca Gimigliano; Giovanni Iolascon (Medicina, 2021)
Muscle injuries occur frequently in athletes, accounting for more than one-third of sport-related trauma. Athletes most affected by these injuries are those practicing football and track and field, with hamstrings and gastrocnemius-soleus as the mainly involved sites. Muscle injuries lead to loss of competitions, long recovery times and risk of re-injury with a consequent increase of the management costs. It is therefore advisable to make an accurate and timely diagnosis to establish appropriate interventions for proper healing in the shortest time. In this context, ultrasound imaging is widely used for diagnosis of musculoskeletal disorders because of several advantages including absence of radiation, portability, good spatial resolution, and the ability to perform dynamic tests. The aim of this review is to address the role of US in the evaluation of athletes with muscle injuries. US may play a pivotal role for the management of sport-related muscle injuries because it is fast and relatively cheap, allowing dynamic muscle assessment and time series evaluation of the healing process.